2016
DOI: 10.1016/j.compositesa.2016.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon nanofiber z-threads on mode-I delamination toughness of carbon fiber reinforced plastic laminates

Abstract: Delamination is a major drawback of carbon fiber reinforced plastics (CFRPs). Studies have reported that carbon nanofibers (CNFs) can improve the delamination toughness of various FRPs. However, lack of CNF alignment control caused substantial uncertainty in the improvements. In this study, a novel CNFs z-threaded CFRP (ZT-CFRP), which utilized z-aligned CNFs as long-range reinforcement threading through the packed carbon fiber bed, was manufactured. The mode-I delamination toughness (G IC) of the ZT-CFRPs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Additionally, another research gap that needs to be more explored is the rate dependency study of delamination in hybrid reinforced composites. In order to address the delamination susceptibility of fiber-reinforced plastics (FRPs), different methods have been studied, including matrix modification by nano-reinforcements [20][21][22][23][24]. It has been frequently reported that the quasi-static G IC of fiber-reinforced epoxies can be increased by adding nanofillers without compromising their outstanding in-plane mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, another research gap that needs to be more explored is the rate dependency study of delamination in hybrid reinforced composites. In order to address the delamination susceptibility of fiber-reinforced plastics (FRPs), different methods have been studied, including matrix modification by nano-reinforcements [20][21][22][23][24]. It has been frequently reported that the quasi-static G IC of fiber-reinforced epoxies can be increased by adding nanofillers without compromising their outstanding in-plane mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been frequently reported that the quasi-static G IC of fiber-reinforced epoxies can be increased by adding nanofillers without compromising their outstanding in-plane mechanical characteristics. Due to their high aspect ratio and superior mechanical properties, Carbon nanofibers (CNFs), as a promising candidate material have been utilized in numerous studies [22][23][24][25][26][27][28]. This extensive research background reveals a good potential for adding CNFs to the pure resin in laminated FRPs as a beneficial and low-cost reinforcing method to improve G IC .…”
Section: Introductionmentioning
confidence: 99%
“…The CFRP prepregs used in this study were fabricated using the methods described in Figure 1; note that these steps are described in further detail by the authors in a previous study [16]. The prepreg manufacturing processes used in this study, including both the hand wet lay-up process (used for the control CFRPs and the UA-CFRPs) and the sponge transfer process (used for the ZT-CFRPs), were performed on single plies of carbon fabric to minimize any potential particle filtering effect.…”
Section: Cfrp Laminate Preparationmentioning
confidence: 99%
“…Previously reported CFRP and CNF zthreaded CFRP composite prepreg manufacturing process data were used to support this study and are available at [doi:10.1016/j.compositesa.2016.10.022]. These prior studies (and datasets) are cited at relevant places within the text as references [16].…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation